IMPROVING STUDENTS’ READING COMPETENCY THROUGH GROUP WORK ACTIVITY WITH MEDIA (CALF) FOR FIFTH GRADE STUDENTS OF SD NEGERI 2 TANGKUP IN ACADEMIC YEAR 2013/2014 - ., Ni Putu Kusni Ratna Cari; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan kemampuan membaca siswa kelas lima SD Negeri 2 Tangkup tahun ajaran 2013/2014 dengan menggunakan Aktifitas Belajar Berkelompok dengan Media (CALF). Dalam penelitian ini terdapat 27 siswa yang terdiri dari 10 laki-laki dan 17 perempuan. Nilai ketuntasan minimum ditentukan dari Kriteria Ketuntasan Minimal yang digunakan sekolah, yaitu 57. Terdapat dua siklus dan tiga sesi untuk setiap siklus; dua sesi untuk memberikan tindakan dan satu sesi untuk memberikan tes evaluasi dan kuesioner. Data diperoleh melalui tes, buku harian peneliti dan kuesioner. Pada tes awal, hanya 26% siswa yang dapat mencapai nilai ketuntasan minimum. Setelah diberikan tindakan pada siklus I, terdapat 66,6% siswa yang mencapai nilai ketuntasan minimum. Jumlah siswa yang mencapai nilai ketuntasan minimum menikat pada siklus II menjadi 100% siswa. Hasil dari buku harian peneliti menunjukkan respon postitif siswa terhadap aktifitas belajar mengajar. Dari hasil kuesioner, Aktifitas Belajar Berkelompok dengan Media (CALF) dapat membantu siswa dalam memahami teks. Dari hasil tersebut diatas, dapat disimpulkan bahwa Aktifitas Belajar Berkelompok dengan bantuan media (CALF) dapat meningkatkan kemampuan membaca siswa khususnya dalam memahami teks untuk siswa kelas lima SD Negeri 2 Tangkup tahun ajaran 2013/2014.Kata Kunci : Membaca, Aktifitas Belajar Berkelompok, Media (CALF) This study was designed in the form of classroom action research which aimed at improving the students’ competency in comprehending text of fifth grade students at SD Negeri 2 Tangkup in academic year 2013/2014 by Group Work Activity with Media (CALF). There were 27 students with 10 males and 17 females. The success indicator was 57 (the standard passing score used by the school). There were two cycles and three sessions for each cycle; two sessions for giving the treatment and one session for giving the post-test and questionnaire. The data were collected through tests, researcher’s diary and questionnaire. From the pre-test, it was found that there were only 26% students could pass the success indicator. After the action given in Cycle I, the students who could pass the success indicator were 66.6% students. The number of students who could pass the success indicator also increased in the Cycle II became 100% students. The result of researcher’s diary showed students’ positive responses toward the activity. From the questionnaire, it was found that group work activity with media (CALF) could help the students in comprehending reading passages. From the result above it could be concluded that Group Work Activity with Media (CALF) could improve the students’ reading competency especially in reading comprehension of fifth grade students at SD Negeri 2 Tangkup in academic year 2013/2014.keyword : Reading Competency, Group Work Activity, Media (CALF)